SISTEM PAKAR DIAGNOSA PENYAKIT KAMBING MENGGUNAKAN METODE FORWARD CHAINING BERBASIS ANDROID - Irwan Adi Pribadi; Agung Adi Candra; Azriansyah Azriansyah (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Goats are livestock that are widely bred by breeders in Indonesia. There are many advantages of raising goats, such as the hair, the milk or sold directly for food needs. In cultivating goats, the average goat owners have less knowledge in terms of diseases that attack their domestic goats. Expert systems began to be used to help an expert or expert in diagnosing disease in goats based on existing symptoms. Objectives and benefits of Diagnosis goat disease, among others, is to facilitate and accelerate knowing the type of disease that attacks the goat. To determine the diagnosis of goat disease, researchers create expert system by applying forward chaining method. Diagnose goat disease using Forward Chaining method. In this study the types of diseases that can be diagnosed as much as 11 diseases. The conclusion of the research that has been done based on the problems that have been resolved through the manufacture of this expert system is expert system to determine goat disease designed with rule base and forward chaining method.